It is not the best option to perform transurethral enucleation of the prostate immediately after biopsy in patients with histological inflammation - Gu, Tengfei; Li, Jie; Chen, Ting; Pan, Yongtao; Sha, Jing (Frontiers in Surgery, 2024)
Objective This study seeks to investigate the impact of histopathological evidence of prostatic histological inflammation (PI) on the surgical outcomes of patients with Benign prostatic hyperplasia (BPH) undergoing transurethral bipolar enucleation of the prostate (BiLEP) following biopsy. Methods We conducted a prospective study in which included 52 patients with histopathological prostatic inflammation (BPH with PI group) and 60 patients with simple BPH (BPH group). Results The study findings indicate that in patients with BPH who underwent BiLEP, various parameters in BPH with PI group including operation time, intraoperative flushing volume, hemoglobin drop value, postoperative white blood cells, postoperative C-reactive protein, and average pain score at 3 days post-operation were significantly higher compared to those in the BPH group (P<0.01). Additionally, the IPSS and IIEF-5 scores of the BPH with PI group were significantly worse before surgery and at 2 weeks post-surgery compared to the BPH group (P<0.01), but no significant differences were observed between the two groups at 1 month and 3 months post-surgery (P>0.05). At the 2-week postoperative, the BPH with PI group exhibited significantly worse outcomes in terms of QOL, PVR, and Qmax compared to the BPH group (P<0.01). However, there were no statistically significant differences between the two groups at 1 month and 3 months post-surgery (P>0.05). The incidence rates of postoperative complications such as fever, prostatic capsule perforation, urinary tract irritation, bladder spasm, acute epididymitis, urinary tract infection, and urethral stricture were higher in the BPH with PI group compared to the BPH group (P<0.05). Nevertheless, there was no significant difference in the overall complication rates between the two groups (P>0.05).There were no statistically significant differences observed between the two groups in postoperative irrigation volume, extubation time, hospitalization time, proportion of secondary operations, proportion of bladder injury and proportion of urinary incontinence (P>0.05). However, the proportion of reported prostate cancer after surgery in the BPH with PI group was significantly higher than that in the BPH group (P<0.05). Conclusion Therefore, it may be advisable to administer a course of anti-inflammatory treatment prior to performing BiLEP in such patients.